The impact of game-based student response system on students’ learning outcomes in narrative writing - Susanti, Yuni Dwi; Wahyuni, Sri (English Dapartment, Faculty of Languages and Arts, Universitas Negeri Semarang, 2022)
This paper is based on research aiming to explore and evaluate the effectiveness of a game-based student response system platform, Kahoot, for teaching narrative writing. By using one group pre-test and post-test design, this quantitative research invited the eleventh-grade students of a senior high school in the academic year of 2021/2022, to actively participate in the project. In this case, the researchers administered a pre-test and post-test for measuring the significant difference in students’ scores, before and after the implementation of Kahoot. Based on the paired sample t-test result, the p-value is 0,000. In addition to that, the t-coefficient is greater than the t-table value, which is 18.436 > 1.690. It means that the difference between students’ skills in writing a narrative text before and after the use of Kahoot, is statistically significant. Specifically, Kahoot could enhance students’ writing in terms of organization, ideas development, grammar, mechanics, and writing style. Since the p-value is less than the significant level or 0,000 < 0,05, and the t-coefficient (18.436) is greater than the t-table (1.690), it can be safely concluded that Kahoot could significantly improve students’ writing skills, specifically in writing a narrative text.